1963
DOI: 10.1002/bit.260050108
|View full text |Cite
|
Sign up to set email alerts
|

Stability of product limited continuous culture systems

Abstract: An investigation was made of the stability of product limited continuous cultures of Saccharomyces carlsbergensis and Pseudomoms ovalis. No oscillations were found in pH or glucose concentration during the steady state, and no overshoot resulted from changing from one steady state to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
1976
1976

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Mateles & Goldthwaite (1963), employing the same medium as Finn & Wilson, observed no oscillations, sustained or damped, in pH or sugar concentration in product-limited continuous culture of S. carlsbergensis or Pseudomonas ovalis; they suggested that their results differed from those of Finn and Wilson because they obtained a continuous record of concentrations whereas Finn and Wilson only had data at discrete sampling times. However, Fiechter & von Meyenburg (1968), using a continuous monitoring device in a study of gas exchange in continuous culture of S. cerevisiae, reported sustained oscillations of gas exchange rate with a period of about 2 h.…”
Section: Introductionmentioning
confidence: 81%
“…Mateles & Goldthwaite (1963), employing the same medium as Finn & Wilson, observed no oscillations, sustained or damped, in pH or sugar concentration in product-limited continuous culture of S. carlsbergensis or Pseudomonas ovalis; they suggested that their results differed from those of Finn and Wilson because they obtained a continuous record of concentrations whereas Finn and Wilson only had data at discrete sampling times. However, Fiechter & von Meyenburg (1968), using a continuous monitoring device in a study of gas exchange in continuous culture of S. cerevisiae, reported sustained oscillations of gas exchange rate with a period of about 2 h.…”
Section: Introductionmentioning
confidence: 81%
“…Reaction (20) denotes the synthesis of G-mass, and the reaction will occur only if G and D are both present in addition to the substrate. Since G-mass is the nucleic acids in the active biomass and D includes enzymatic proteins, reaction (20) may be taken to be an overall representation of the biochemical steps in the synthesis of the nucleic acids. Reaction (21) denotes the synthesis of D-mass, and the interaction will occur only in the presence of both G and D in addition to the substrate.…”
Section: The Modelmentioning
confidence: 99%
“…(22) and (23) are second-order processes since this would be the simplest representation for reactions involving two reactants. I n order to represent interactions (20) and (21) Based on two different mechanisms of inhibitor formation, two models, denoted 1 and 2, have been analyzed. .…”
Section: The Modelmentioning
confidence: 99%